“Less lethal” violence: police, discourse, pacification - Walrath, Nicholas Timothy (Kansas State University, 2022)
Public discussions of police violence tend to fixate upon seemingly exceptional cases of lethal violence: Eric Garner choked to death by the NYPD, Michael Brown shot dead in Ferguson, Derek Chauvin’s knee on George Floyd’s neck, the list grows. While necessary, the focus on lethal violence performs the trick of minimizing “non-lethal” violence, hiding it in plain sight. This is in part accomplished through discourses which frame violence and injuries not as the misdeeds of police, but as the consequences of the behavior of protesters, agitators, and other “disrupters.” To broaden the critique of police violence and the police power beyond lethality, this project focuses on the use of “less-than-lethal” weaponry (LLW) in the context of the 2020 protests. Focusing on this overlooked, perhaps under-theorized form of violence problematizes the neat dichotomy between lethal and non-lethal. From the murder of journalist Ruben Salazar by a “less lethal” tear gas missile, the 1992 LA riots where rubber bullets were first fired by the LAPD to the summer of 2020, where it again fired less lethal munitions into crowds, the project demonstrates how public protest registers as inimical to the LAPD. Hence, this research explores by what ways, if any, less lethal as a concept expands the police’s ability to administer violence by negotiating and depicting this potential through appeals to reform as well as narrow understandings of acceptable protests and police violence.
Keywords: Less lethal; Reform; Pacification